Microwave-assisted Synthesis of Bis(4-hydroxy-3-methoxybenzylidene)cyclopentanone using Ba(OH)2.8H2O as a Base Catalyst - Gunawan, Maggie Anastasya; Budiati, Tutuk; Soewandi, Ami (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2026)
Background: Synthetic curcumin analogs have been widely studied due to their pharmacological activity. One of the curcumin analog compounds, namely 2,5-bis(4-hydroxy-3-methoxybenzylidene)cyclopentanone (HM-BCP), which has more potent anti-inflammatory activity than curcumin.. In the synthesis process, the presence of the OH-phenolic group is still a problem to maximize the reaction condition. The use of strong base catalysts may cause unwanted side reactions with the phenolic OH group present in the substrate. Therefore, barium hydroxide was used as the catalyst because it has lower basicity than NaOH, which is commonly used in this reaction. Objective: This study aims to synthesize HM-BCP using Ba(OH)2.8H2O as a catalyst in several concentrations. The reaction was assisted by microwave irradiation. Methods: Synthesis of HM-BCP from cyclopentanone and vanillin via Claisen-Schmidt condensation in alkalis condition. Cyclopentanone, vanillin, and Ba(OH)₂·8H₂O were mixed for 15 min, followed by microwave irradiation (480 W, 10 min). The reaction mixture was stirred for 5 min after each minute of irradiation. The reaction product was analyzed by TLC to determine the area percent ratio of the starting material (vanillin), and HM-BCP. The purity of the synthesized products were tested using TLC and melting point determination, while structure identification by IR and H-NMR spectroscopic methods. Results: The use of 2–4 molEq of Ba(OH)₂ as the catalyst in the synthesis of HM-BCP produced relative percentage areas of 11.4%, 15.8%, and 20.9%, respectively. Conclusion: Barium hydroxide has been shown to act as a catalyst in the synthesis of HM-BCP via Claisen-Schmidt condensation but optimization of reaction conditions is needed.